Plan de negocio para la creación de un supermercado de mariscos en el cantón Quevedo provincia de los Ríos, año 2013 - Murillo Córdova, Maicol Pedro (2013)
Companies today must generate activities to improve its organizational structure and intensify the administrative system, plus sales and financial system through established procedures in decision making process, competitive strategies in a changing and globalized economy makes the present research is focused on investigating the implementation of a supermarket seafood in the city of Quevedo, bearing in mind the administrative activities and financial and business to verify their financial position, profitability and development over the competition. . In the market there are different ways and means of conducting business, the same as going from the empirical method that is preceded by experience in this type of family business, a consolidated structures developed with entrepreneurs and small businesses with technical knowledge of the processes study. The different paradigms of sales and marketing employees in the middle there is always the prospect that this business has little time to market, absorbed by unfair competition from big business trying to monopolize the market. Within this context set out to answer the following research question: Will you allow a business plan, developing a Seafood Supermarket, identifying a potential market and consumer needs, from the year 2013? The general objective for this research is raised: Develop the structure of a business plan for the creation of a Supermarket in Canton Seafood Quevedo, 2013, its main objectives: Identify business were offered through seafood Supermarkets in Canton Quevedo, performing a market study to determine the demand for the creation of a supermarket seafood and developed a technical, economic and financial feasibility of assessing the creation of a supermarket in Canton Seafood Quevedo, year 2013. In this way and by hypothesis was evident if the improper marketing process seafood business Quevedo Canton, positive impact for the development of a Business Plan for Creating a Seafood Supermarket. It should be noted that the research was based on a descriptive and applied research aimed at studying, analyzing, describing and if necessary change the reality of the present nature of the problem under study. Further research was supported by the use of techniques such as interviews and survey where information is sought and provided directly to draw conclusions that are in high demand, therefore considered feasible opening supermarket seafood Quevedo City as the technical and financial report gives a proposal is viable because it has all the necessary tools to carry out the calculated values: NPV = $ 525,149; IRR = 219%, are considered to justify amounts development and viability of this project, which will serve the residents of Canton and to produce positive Quevedo socioeconomic progress thereof.